Cultural tourism, place branding, and sustainable development: The role of community engagement, visitor’s satisfaction and environmental awareness - Aidoo, Gertrude Sarah; Kwaning, Collins Owusu; Opoku, Ababio Kwaku; Owusu, Ackah; Ansah, Victoria Owusu –; Afriyie, Emelia Ohene (Edelweiss Applied Science and Technology, 2024)
This study examines the role of cultural tourism and place branding in fostering sustainable tourism development, focusing on community engagement, visitor satisfaction, and environmental awareness. Using Sustainable Development and Cultural Capital theories as the theoretical foundation, the research highlights the long-term benefits of tourism and the significance of local culture and heritage in achieving sustainable outcomes. A quantitative methodology was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from participants at a cultural festival in Takoradi, Ghana. The findings reveal that place branding significantly impacts sustainable development, both directly and indirectly, through visitor satisfaction. Additionally, cultural tourism promotes sustainable development via community engagement, with environmental awareness moderating the relationship between community engagement and sustainable development. This study offers valuable insights for policymakers and tourism practitioners, emphasizing the integration of cultural assets and community involvement in sustainable tourism strategies. By exploring the interplay between cultural tourism, place branding, and sustainability, the research adds a unique perspective to the field of sustainable tourism development.